Social Loafing and its Relation to the Personality Traits of Kindergarten Teachers: ابتسام سعيد احمد (Journal of the College of Education for Women, 2020)
The research seeks to know the social loafing of kindergarten teachers and their relation to personality traits. In order to achieve the research objectives, the researcher constructed the social loafing scale, which she applied to kindergarten teachers. The scale consists of (22) paragraphs. It has good credibility and stability. The coefficient of stability (85.0) was the retest method and (81.0) Alpha Cronbach equation. In addition, the researcher has adopted (Raymond Cattel) personality traits scale, which has been adapted to the Arab environment (Abdel Rahman and Abu Abada,1998), The scale consists of (39) paragraphs, and enjoys the apparent honesty. The measure of social loafing and the measure of personality traits was applied to a sample of (200) teachers, who were chosen in a simple random way. The research reached the following results:Kindergarten teachers have a social loafing breakdown at varying levels.The four character traits are available to teachers at different levels.Social loafing is linked to the personality traits of the teachers in a high and positive relationship.Then the researcher submitted a set of recommendations and proposals.